2019
DOI: 10.3389/fonc.2019.00486
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-126 Is a Tumor Suppressor of Granulosa Cell Tumor Mediated by Its Host Gene EGFL7

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression at a post-transcriptional level. We examined the role of miR-126 in granulosa cell tumor (GCT) of the ovaries. In tissues from malignant GCT patients miR-126 expression was repressed. We showed that miR-126 could inhibit proliferation, migration, hormone production and promote apoptosis of cancerous granulosa cells (GCs) in vitro . The role of miR-126 as “tumor suppressor” was confirmed by using a tumor formation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Some miRNAs play distinct roles in different types of cancers. miR-126 originally recognized as endothelial-specific miRNA plays an essential role in angiogenesis and vascular integrity [25] and has been shown to function as a critical tumor suppressor in various solid tumors [26,27]. In contrast, it has been demonstrated that miR-126 is aberrantly expressed and reported to possess a oncogenic role in core binding factor leukemia [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs play distinct roles in different types of cancers. miR-126 originally recognized as endothelial-specific miRNA plays an essential role in angiogenesis and vascular integrity [25] and has been shown to function as a critical tumor suppressor in various solid tumors [26,27]. In contrast, it has been demonstrated that miR-126 is aberrantly expressed and reported to possess a oncogenic role in core binding factor leukemia [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-126-3p located in the host gene of epidermal growth factor domain 7 (EGFL7) of human chromosome 9q34.3, was also involved in different rearrangements in various cancers ( 61 ). One of the most notable targets in lung cancer is EGFL7 ( 62 , 63 ). The functions of miR-126-3p ranged from angiogenesis to cell proliferation regulation ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through miRNA profiling, juvenile- and adult-derived cell-lines have been shown to be biologically distinct, but this still needs to be addressed in vivo. Different studies by Tu et al showed that miR-10a promotes granulosa cell tumor development via the PTEN-AKT/Wnt regulatory axis, while miR-126 is a tumor suppressor of granulosa cell tumor development via the regulation of EGFL7 [ 72 , 73 ].…”
Section: Dysregulation Of Mirnas In Rare Gynecological Cancersmentioning
confidence: 99%
“…miR-9 [ 55 ], miR-10a [ 73 ], miR-21 [ 126 ], miR-590-5p [ 108 ], miR-3147 [ 110 ] and miR-4712 [ 109 ] have been described as “oncomiRs” across multiple mammalian cell types, which is consistent with their role in RGCs. In addition, underexpressed miRNAs in RGCs such as miR-34 [ 124 ], miR-126 [ 72 ] and miR-196b [ 125 ] act as tumor suppressors.…”
Section: A Brief Overview On Mirnas and Their Regulated Targets In Rgcsmentioning
confidence: 99%
See 1 more Smart Citation